George W. Hess, Revised Ordinances of the City of Evanston: Also Special Laws and Ordinances of General Interest 131 (1893) - (:unkn) unknown (My University, 1893)
§ 531, § 535: Prohibited concealed carry of any pistol, colt, slung shot, cross knucklet, knuckles of lead, brass or other metal, Bowie-knife, dirk, dagger, or any other dangerous or deadly weapon. Violators fined not less than five nor more than two hundred dollars.
Keywords: CARRY - CONCEALED